Cumulative radiation exposure from imaging procedures and associated lifetime cancer risk for patients with lymphoma - Fabritius, Grete; Klein, Stefan; Popp, Henning; Meyer, Mathias; Glatting, Gerhard; Henzler, Claudia; Hofmann, Wolf-Karsten; Schönberg, Stefan; Henzler, Thomas (Scientific reports, 2016)
The aim of this study was to systematically evaluate the cumulative radiation exposure and the associated lifetime-cancer-risk from diagnostic imaging in patients with Hodgkin-lymphoma-(HL) or diffuse-large-B-cell-lymphoma (DLBCL). 99 consecutive patients (53-males) diagnosed with HL or DLBCL were included in the study and followed. Based on the imaging reports, organ and effective-doses-(ED) were calculated individually for each patient and the excess lifetime risks were estimated. The average ED in the first year after diagnosis was significantly different for men (59 ± 33 mSv) and women (74 ± 33 mSv)-(p < 0.05). The mean cumulative ED in each of the following 5 years was 16 ± 16 mSv without significant differences between men and women-(p > 0.05). Over all years, more than 90% of the ED resulted from CT. The average cumulative radiation risk estimated for the first year was significantly lower for men (0.76 ± 0.41%) as compared to women (1.28 ± 0.54%)-(p < 0.05). The same was found for each of the subsequent 5-years (men-0.18 ± 0.17%; women-0.28 ± 0.25%)-(p < 0.05). In conclusion, for HL and DLBCL patients investigated in this study, a cumulative radiation risk of about 1 excess cancer per 100 patients is estimated for diagnostic imaging procedures performed during both the first year after diagnosis and a follow-up period of 5 years.
Gesehen am 04.07.2019